Comparison of superior and inferior division occlusions treated with endovascular thrombectomy - Seker, Fatih; Pfaff, Johannes; Neuberger, Ulf; Schieber, Simon; Nagel, Simon; Ringleb, Peter A.; Bendszus, Martin; Möhlenbruch, Markus Alfred (Clinical neuroradiology, 2019)
Several studies have shown that thrombectomy is safe and effective in occlusions of the M2 segment of the middle cerebral artery. This retrospective study compared superior and inferior division occlusions regarding radiological and clinical outcomes.
Gesehen am 14.04.2020